Endometriosis-associated ovarian cancer: A ten-year cohort study of women living in the Estrie Region of Quebec, Canada - Aris Aziz (BMC, 2010)
Abstract Objectives Endometriosis has been believed to increase the risk of developing ovarian cancer, but recent data supporting this hypothesis are lacking. The aim of this study was to verify whether the incidence of endometriosis, ovarian cancer and the both increased during the last 10 years among women living in the Estrie region of Quebec. Methods We collected data of women diagnosed with endometriosis, ovarian cancer or both, between 1997 and 2006, from a population living in the Estrie region of Quebec. We performed this retrospective cross-sectional study from the CIRESSS (Centre Informatisé de Recherche Évaluative en Services et Soins de Santé) system, the database of the CHUS (Centre Hospitalier Universitaire of Sherbrooke), Sherbrooke, Canada. Results Among the 2854 identified patients, 2521 had endometriosis, 292 patients had ovarian cancer and 41 patients had both ovarian cancer and endometriosis. We showed a constant increase in the number of ovarian cancer (OC) between 1997 and 2006 (r2 = 0.557, P = 0.013), which is not the case for endometriosis (ENDO) or endometriosis-associated ovarian cancer (EAOC). The mean age ± SD was 40.0 ± 9.9 and 53.9 ± 11.4 for patients having ENDO and OC, respectively. Mean age of women with EAOC was 48.3 ± 10.8, suggesting an early onset of ovarian cancer in women having endometriosis of about 5.5 years average, P = 0.003. Women with ENDO were at increased risk for developing OC (Rate Ratio [RR] = 1.6; 95% Confidence Interval [CI] = 1.12-2.09). Pathological analyses showed the predominance of endometrioid type (24.4%) and clear-cell type (21.9%) types in EAOC compared to OC, P = 0.0070 and 0.0029, respectively. However, the serous type is the most widespread in OC (44.5%) in comparison to EAOC (19.51%), P = 0.0023. Conclusion Our findings highlight that the number of cases of ovarian cancer is constantly increasing in the last ten years and that endometriosis represents a serious risk factor which accelerates its apparition by about 5.5 years.